Association between breastfeeding and better preserved cognitive ability in an elderly cohort of Finnish men. Issue 6 (22nd August 2017) - Rantalainen, V.; Lahti, J.; Henriksson, M.; Kajantie, E.; Mikkonen, M.; Eriksson, J. G.; Raikkonen, K.
Abstract : Background: Being breastfed in infancy has been shown to benefit neurodevelopment. However, whether the benefits persist to old age remains unclear. Methods: We examined the associations between breastfeeding and its duration on cognitive ability in young adulthood and old age, and on aging-related cognitive change over five decades. In total, 931 men from the Helsinki Birth Cohort Study born in 1934–1944 in Finland took the Finnish Defence Forces Basic Intellectual Ability Test (total and verbal, arithmetic and visuospatial subtest scores) twice, at ages 20.2 and 67.9 years, and had data on breastfeeding (yes v. no) and its duration ('never breastfed', 'up to 3', '3 to 6' and '6 or more months'). Linear and mixed model regressions tested the associations. Results: At 20.2 years, breastfed men had higher cognitive ability total and visuospatial subtest scores [mean differences (MDs) ranged between 3.0–3.9, p values < 0.013], and its longer duration predicted higher cognitive ability total and arithmetic and visuospatial subtest scores (MDs ranged between 3.0 and 4.8, p values < 0.039). At 67.9 years, breastfed men had higher total cognitive ability and all subtest scores (MDs ranged between 2.6 and 3.4, p values < 0.044) and its longer duration predicted all cognitive ability scores (MDs ranged between 3.1 and 4.7, p values < 0.050). Verbal subtest scores decreased over five decades in men who were never breastfed or were breastfed for 3 months or less, and increased in those breastfed for longer than 3 months. Conclusions: Neurodevelopmental advantages of breastfeeding and its longer duration persist into old age, and longer duration of breastfeeding may benefit aging-related change, particularly in verbal reasoning ability.